Psilocybin-assisted therapy for reducing alcohol intake in patients with alcohol use disorder: protocol for a randomised, double-blinded, placebo-controlled 12-week clinical trial (The QUANTUM Trip Trial) - Claus Thorn Ekstrøm; Patrick MacDonald Fisher; Gitte Moos Knudsen; Dea Siggaard Stenbæk; Anders Fink-Jensen; Mathias Ebbesen Jensen; Tobias Søgaard Juul (BMJ Open, 2022)
Introduction Alcohol use disorder is a difficult-to-treat psychiatric disorder and a major burden on public health. Existing treatment efficacy is moderate, and relapse rates are high. Preliminary findings suggest that psilocybin, a psychedelic compound, can safely and reliably occasion highly meaningful experiences that may spur a positive change in drinking behaviour when administered in a therapeutic context. However, the efficacy of a single psilocybin administration and its potential neurobiological underpinnings still remain unknown.Methods and analysis To establish efficacy, we will investigate the effects of psilocybin-assisted therapy versus placebo in a randomised, double-blinded, placebo-controlled 12-week clinical trial. Ninety treatment-seeking patients, aged 20–70 years, diagnosed with alcohol use disorder will be recruited from the community via advertisement and referrals from general practitioners or specialised treatment units. The psilocybin or placebo will be administered in accordance with a protocol for psychological support before, during and after the dosing. Outcome assessments will be carried out 1, 4, 8 and 12 weeks postdosing. The primary outcome is reduction in the percentage of heavy drinking days from baseline to follow-up at 12 weeks. Key secondary outcomes are as follows: (1) total alcohol consumption, (2) phosphatidyl-ethanol, an objective biomarker for alcohol, (3) plasma psilocin, the active metabolite, to establish a possible therapeutic range, (4) the acute subjective drug experience as a possible predictor of treatment outcome and (5) neuronal response to alcohol cues and cognitive flexibility within corticostriatal pathways by use of functional MR brain imaging 1-week postdosing.Ethics and dissemination Ethical approval has been obtained from the Committee on Health Research Ethics of the Capital Region of Denmark (H-20043832). All patients will be provided oral and written information about the trial before screening. The study results will be disseminated by peer-review publications and conference presentations.Trial registration number EudraCT 2020-000829-55 and NCT05416229.